2010
DOI: 10.1093/ije/dyq020
|View full text |Cite
|
Sign up to set email alerts
|

LiST as a catalyst in program planning: experiences from Burkina Faso, Ghana and Malawi

Abstract: Background African countries are working to achieve rapid reductions in maternal and child mortality and meet their targets for the Millennium Development Goals (MDGs). Partners in the Catalytic Initiative to Save One Million Lives (CI) are assisting them by providing funding and technical assistance to increase and accelerate coverage for proven interventions. Here we describe how the Lives Saved Tool (LiST) was used as part of an early assessment of the expected impact of CI plans in Malawi, Burkina Faso and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 1 publication
0
40
0
2
Order By: Relevance
“…For example, in 2003, 54% of children with fever in well-off families were treated in public health centres, while this proportion was only 22% for children in poor families 9. A recent simulation suggested that child mortality might be reduced by up to 20% if the proportion of children treated in health centres for malaria, respiratory infections and diarrhoea were increased 10. The results of the most recent Demographic and Health Survey showed that in 2010 only half of the children with one of these three conditions were treated in health centres 11.…”
Section: Context and Interventionmentioning
confidence: 99%
“…For example, in 2003, 54% of children with fever in well-off families were treated in public health centres, while this proportion was only 22% for children in poor families 9. A recent simulation suggested that child mortality might be reduced by up to 20% if the proportion of children treated in health centres for malaria, respiratory infections and diarrhoea were increased 10. The results of the most recent Demographic and Health Survey showed that in 2010 only half of the children with one of these three conditions were treated in health centres 11.…”
Section: Context and Interventionmentioning
confidence: 99%
“…Globally, most of the deaths of children under the age of five are due to a limited number of causes, with pneumonia and diarrhoea as the main killers [2]. This is despite the fact that the timely recognition of danger signs, with appropriate care seeking, and the administration of simple drugs such as oral antibiotics, oral rehydration solutions (ORS), and zinc could prevent most of these deaths [3]. Efforts have been made to implement this knowledge, which has contributed to the rapid improvements in child survival.…”
Section: Introductionmentioning
confidence: 99%
“…The correct treatment of childhood pneumonia, diarrhea, and malaria is one of the most powerful interventions for reducing mortality 1. However, in most countries with high mortality rates, facility-based services alone do not provide adequate access to treatment,2,3 and most importantly not within the crucial window of 24 hours after onset of symptoms.…”
Section: Bringing Treatment Closer To Homementioning
confidence: 99%